Determinants of Zakat Payment Attitude and Its Impact on Muslims’ Acceptance of Zakat as a Tax Deduction: Evidence from Indonesia - Setiawan bin Lahuri; Izlawanie Muhammad; Husnul Khotimah; Ainun Amalia Zuhroh; Murad Ali Al-Zaqeba (Emerald Publishing Limited, 2026)
Indexed by Scopus